Aspects of substantial compliance and strict compliance as applied to demand guarantees - Sikobi, Nkanyiso (University of South Africa, 2024)
Demand guarantees are essential for purposes of commerce and are used to secure the performance of the contractor. South African courts have held that demand guarantees are akin to letters of credit. Despite the independent nature of demand guarantees to the underlying contract, in circumstances where the beneficiary has made a fraudulent claim, the guarantor may dishonour the demand or claim. South African courts have indicated that if the underlying contract is illegal, courts may intervene by granting an interdict to stop payment under the guarantee. The South African law recognises traditional guarantees (often called suretyship) where the beneficiary, when making a demand or claim, must demonstrate liability on the part of the contractor. There are instances where courts have held that guarantees were of a nature akin to suretyship. In South Africa, parties entering into a demand guarantee contract are subject to the common law of contract. The Uniform Rules for Demand Guarantees, adopted by the International Chamber of Commerce, are only applied by explicit reference in the demand guarantee failing which such rules do not apply. Non-implementation of these rules has resulted in rigorous litigation in the recent years on this subject-matter. A demand must be supported by documents and require strict conformity. However, strict compliance with the prerequisites of the demand guarantee has not been applied consistently in South Africa. South African courts have recently been applying substantial compliance, in certain circumstances finding that a term in a guarantee is just directory and not obligatory. Furthermore, on many occasions, courts have deviated from strict compliance holding that a term in a guarantee does not make commercial sense thus such term is not mandatory. In this way, courts apply the most business-sensible interpretation when interpreting demand guarantees.
Keywords: Autonomous; Beneficiary; Contractor; Demand guarantees; Demand or conditional guarantee; Documentary letters of credit; Employer; First written demand; Fraud and illegality exception; Guarantor; Independence; Performance guarantees; Security for performance; Strict compliance; Substantial compliance; Suretyship; Underlying contract; Uniform rules for demand guarantees

Les sûretés négatives - Ndiaye, Paul Babou (Université Assane Seck de Ziguinchor, 2017)
Keywords: Clause d’inaliénabilité; Clauses de sûretés; Créances; Droits réels; Inexécution contractuelle; Negative pledge clauses; Sûreté négative; Sûretés

La compétitivité de l'hypothèque maritime dans le cadre du financement de navires - Laporte, Sophie (Aix-Marseille Université, 2015)
S'interroger sur l'attractivité de l'hypothèque maritime en France suppose de la mettre en contact avec le mortgagede droit anglais (Partie I). Dès lors, à l'issue de l'étude de l'hypothèque conviendra-t-il de s'interroger sur l'opération de fiducie-sûreté appliquée au financement de navire (Partie II).

Cessão da garantia bancária autónoma: uma reflexão à luz do direito santomense - Jesus, Waldemar Eduardo (Universidade Nova de Lisboa, 2014)
La cession de la garantie bancaire autonome, est sans doute un aspect de la plus grande pertinence pour le cessionnaire d'un crédit accordé, c’est un autre moyen que le commerce, «máxime», le commerce international met à ses exploitantes ou ses operateurs pour obtenir de la liquidité. Nous espérons avec ce travail, d'analyser l'applicabilité de la garantie bancaire autonome, en partant du principe selon lequel en cas de transfert de crédit, les respectives garanties et autres accessoires également se transmettent. Basé sur la doctrine internationale, notamment italienne et portugaise, nous avons l'intention de parvenir à une solution que permet une application correcte de l'institut concerné, dans le cadre droit Santoméen, c'est à dire, c'est qui permet au cessionnaire d'une créance de protéger, effectivement, ses intérêts légitimes. A cessão da garantia bancária autónoma é, sem dúvida, um aspeto da maior relevância para o cessionário de um determinado crédito pois, é mais um meio que o comércio, «máxime», o comércio internacional dispõe aos seus operadores para obter a liquidez. Pretendemos com o presente trabalho, analisar a aplicabilidade à garantia bancária autónoma do princípio segundo o qual, em caso de transmissão de um crédito as respetivas garantias e outros acessórios também se transmitem. Com base na doutrina internacional, sobretudo italiana e portuguesa, pretendemos chegar uma solução que permita boa aplicação do instituto em causa na ordem jurídica santomense, isto é, que permita ao cessionário de um crédito salvaguardar, efetivamente, os seus legítimos interesses.
Keywords: Cession; Cessão; Crédit; Crédito; Garantia bancária autónoma; Garantie bancaire autonome; L’ordre juridique Santoméen; Ordem jurídica santomense